Investigation on mechanical behaviors of Self-compacting concrete containing reclaimed asphalt pavement. (5th September 2022) - Liu, He; Duan, Guangchao; Wang, Fengchi; Zhang, Jingyi; Zhou, Yewang; Feng, Yufei; Zhang, Kexin
Graphical abstract: Highlights: Stress–strain relationship Characteristics of SCC with different RAP contents are revealed. Crack propagation of SCC with different RAP contents is presented. Damage constitutive model is established under uniaxial compression. Abstract: In order to investigate the effect on mechanical properties of self-compacting concrete (SCC) with reclaimed asphalt pavement (RAP), SCC samples with RAP content of 0%, 30%, 60%, 90%, and 100% by weight were prepared. The stress–strain relationship and crack propagation mechanisms were researched by the uniaxial compression test and digital speckle correlation technique. Furthermore, a compression damage constitutive model was established. The results show that RAP has an apparent negative influence on workability and compressive strength of SCC with RAP content ranging from 0% to 100%. Peak stress and elastic modulus of SCC samples decrease with RAP content increase while peak strain of samples increases. The cracks number of the specimens increases significantly and energy absorption ability is improved with RAP content increase. The proposed damage constitutive model effectively describes the strain–stress characteristics of self-compacting concrete with different RAP contents and the results agreed well with experimental tests. The change rate of damage variable constantly decreases with RAP content increase.